Le passé/présent entre dictature et transition politique dans la société paraguayenne contemporaine - Luc Capdevila (Centre de Recherches sur les Mondes Américains, 2008)
In comparison with the recent evolution that the republics of South America know, Paraguay suffered during its democratization process. So, in a context of relative political inertia, it is significant to question the potential adjustments in the relation that society maintains with the past, since the history was one of the central pieces of the system of framing and “enfermement” of the dictatorship.It is thus a question of questioning in what sens a change of political régime induce a change of mode of historicity. We will put the attention first on the tensions between official history and collective memory under the dictatorship in order to define the mode of historicity which was specific to this culture, in order to understand afterwards the current inertia of representation of the past, and to identify what could correspond today to a mode of historicity of transition.